2003
DOI: 10.1167/iovs.03-0080
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Specificity of Immunoprotective Therapeutic Vaccination for Glaucoma

Abstract: To benefit damaged neurons, immune neuroprotection should be directed against immunodominant antigens that reside in the site of damage. In a rat model of high IOP, RGCs can benefit from vaccination with peptides derived from proteins that are immunodominant in the eye but not from myelin-associated proteins. This suggests that the site of primary degeneration in IOP-induced RGC loss is in the eye. Cop-1 vaccination apparently circumvents the site-specificity barrier and provides protection without risk of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 37 publications
2
58
0
Order By: Relevance
“…It was recently suggested that this compound can activate a wide range of self-reactive T cells (20,21). In a model of a chronic neurodegenerative disorder associated with optic nerve neuropathy, such as glaucoma, Cop-1 vaccination was found to bypass the tissue-specificity barrier imposed by antigens residing in the damaged tissue (15,22) and to significantly increase neuronal survival (15,20).…”
mentioning
confidence: 99%
“…It was recently suggested that this compound can activate a wide range of self-reactive T cells (20,21). In a model of a chronic neurodegenerative disorder associated with optic nerve neuropathy, such as glaucoma, Cop-1 vaccination was found to bypass the tissue-specificity barrier imposed by antigens residing in the damaged tissue (15,22) and to significantly increase neuronal survival (15,20).…”
mentioning
confidence: 99%
“…For instance, copolymer-1 could be used as a vaccine as it is an antigen that cross responds with a widespread array of T-cells, and can provoke a defensive immune reaction to shield retinal ganglion cells from cell mortality initiated by toxins or improved Intra ocular Pressure (Bakalash et al, 2003). A fundamental concern for planning neuro-defensive vaccines is the position of protection.…”
Section: Neuro Defensive Vaccinesmentioning
confidence: 99%
“…A fundamental concern for planning neuro-defensive vaccines is the position of protection. Some recommended that the focus should be in the retinal ganglion cells and not in the optical nerves because in the initial glaucomatous phase cell fatality stimulated by higher intra ocular pressure that arises in the retinal ganglion cells, not in the optical nerve (Bakalash et al, 2003). R16, a peptide derivative from the retinal ganglion cell, is one paradigm of a neuro-protecting vaccine.…”
Section: Neuro Defensive Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…R 16, a peptide derived from the RGC, is one example of a neuroprotective vaccine. Although R16 can cause slight RGC death for those without glaucoma, the benefit from this treatment far exceeded the damage from untreated glaucoma conditions (21).…”
Section: Neuroprotective Vaccinesmentioning
confidence: 99%